Xerostomia in the older adult population, from diagnosis to treatment: a literature review - Campos, Wladimir Gushiken de (2019)
Saliva is important for the preservation and maintenance of normal physiological conditions of oral tissues, and factors influencing its decrease are associated with the risk for oral diseases. Xerostomia is the subjective sensation of oral dryness, which can be influenced by etiological factors including the use of several types of medications, Sjogren’s and metabolic syndromes, head and neck irradiation, among others. Treatment methods for xerostomia vary and can be local or systemic. The aim of this article is to present the results of a literature review addressing the correlation between xerostomia and its incidence and prevalence in the older adult population. Results of this review highlight the importance of diagnosis and appropriate management, and briefly describe treatment modalities and etiological factors such as medications, Sjogren’s syndrome, metabolic syndrome, and head and neck irradiation.